New Perspectives on Inequality in Latin America - Manuel Fernández; Gabriela Serrano (Institute of Labor Economics (IZA), 2022)
Latin American countries have some of the highest levels of income inequality in the world. However, earnings inequality significantly changed over the last three decades, increasing during the 1980s and 1990s, declining sharply in the 2000s, and stagnating or even increasing in some countries during the last decade. Macroeconomic instability in the region in the 1980s and early 1990s, and the introduction of structural reforms like trade, capital, and financial liberalization, affected the patterns of relative demand and relative earnings across skill-demographic groups in the 1990s, increasing inequality. Significant gains in educational attainment, the demographic transition, and rising female labor force participation changed the skill-demographic composition of labor supply, pushing education and experience premium downward, but this was not enough to counteract demand-side trends. At the turn of the century, improved external conditions, driven by China's massive increase in demand for commodities boosted economies across Latin America, which began to grow rapidly. Growth was accompanied by a positive shift in the relative demand for less-educated workers, stronger labor institutions, rising minimum wages, and declining labor informality, a confluence of factors that reduced earnings inequality. In the aftermath of the global financial crisis, particularly after the end of the commodities price boom in 2014, economic growth decelerated, and the pace of inequality decline stagnated. There is extensive literature trying to explain the causes of earnings inequality dynamics during the last three decades in Latin America. We discuss this literature regarding themes, methodological approaches, and key findings, emphasizing the latest perspectives. The focus is on earnings inequality and how developments in labor markets have shaped it.
Keywords: D31; D33; F16; J21; J23; J31; O54; 330; inequality; Latin America; education premium; experience premium; trade reforms; minimum wage; informality